Successful production of genome-edited rats by the rGONAD method - Kobayashi, Tomoe (BMC Biotechnol, 2018)
BACKGROUND: Recent progress in development of the CRISPR/Cas9 system has been shown to be an efficient gene-editing technology in various organisms. We recently developed a novel method called Genome-editing via Oviductal Nucleic Acids Delivery (GONAD) in mice; a novel in vivo genome editing system that does not require ex vivo handling of embryos, and this technology is newly developed and renamed as “improved GONAD” (i-GONAD). However, this technology has been limited only to mice. Therefore in this study, we challenge to apply this technology to rats. RESULTS: Here, we determine the most suitable condition for in vivo gene delivery towards rat preimplantation embryos using tetramethylrhodamine-labelled dextran, termed as Rat improved GONAD (rGONAD). Then, to investigate whether this method is feasible to generate genome-edited rats by delivery of CRISPR/Cas9 components, the tyrosinase (Tyr) gene was used as a target. Some pups showed albino-colored coat, indicating disruption of wild-type Tyr gene allele. Furthermore, we confirm that rGONAD method can be used to introduce genetic changes in rat genome by the ssODN-based knock-in. CONCLUSIONS: We first establish the rGONAD method for generating genome-edited rats. We demonstrate high efficiency of the rGONAD method to produce knock-out and knock-in rats, which will facilitate the production of rat genome engineering experiment. The rGONAD method can also be readily applicable in mammals such as guinea pig, hamster, cow, pig, and other mammals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12896-018-0430-5) contains supplementary material, which is available to authorized users.